Pendekatan Kualitatif dalam Ilmu Sejarah: Sebuah Telaah Konseptual - Arditya Prayogi (Historia Madania: Jurnal Ilmu Sejarah, 2021)
The popularity of the qualitative approach has recently increased. Especially in the social sciences (including the humanities), where this approach has its own place, although, the most important substance in science, namely the theory itself, is actually qualitative. This is further strengthened by the essence of a qualitative approach (in the social sciences of the humanities) which emphasizes the investigation of a social phenomenon and human problem. This article describes how a qualitative approach is used (particularly) in the science of history, as well as the various characteristics inherent in qualitative research which is so closely related to the science of history. This article was written using descriptive analytical method supported by literature study as the data mining process. From the results of the description, it is known that history as a family of humanities will inevitably (still) use a qualitative approach in its scientific description. This qualitative approach is in the form of a narrative-descriptive-analytical explanation of history, which makes history, apart from being a science, also a story. The task of history is to tell stories through narrative texts, so that a qualitative approach is embedded in the science of history.Keywords: Approach, Qualitative, Historical Science